Effect of Fermentation Time and Weight of Bread Yeast on Bioethanol Content from Glucose Hydrolysis of Cellulose Empty Bunches Palm Oil (Elaesis guineensis Jacq.) with HCl 30% - Rahman, Rozyanti (Talenta Publisher, 2022)
Research about the effect of fermentation time and weight of yeast bread on bioethanol concentration from the fermentation of the glucose from hydrolysis of cellulose oil palm empty fruit bunches (Elaeis guineensis Jack ) with HCl 30% has been done. From the research, it found that oil palm empty fruit bunches contained cellulose of 24.1298 %. The cellulose was isolated from oil palm empty fruit bunches. It was hydrolyzed by HCl 30% to yield glucose and was analyzed by Nelson-Somogyi Method and the rate of the glucose was 17,1051 %. The fermentation of glucose used various periods of fermentation were 2 days, 4 days, and 6 days and various added baker yeast were 2 g, 4 g, and 6 g. The percentage of bioethanol was analyzed by using potassium dichromate titrations of the oxidation volumetric method. The result of the analysis shows that the highest percentage was 7.3922% with a period of fermentation was 6 days and baker yeast of 6 g.